Foliar Spraying of Silicon Associated with Salicylic Acid Increases Silicon Absorption and Peanut Growth - Souza Junior, Jonas Pereira de [UNESP]; Frazao, Joaquim Jose [UNESP]; Barros de Morais, Thais Chagas [UNESP]; Degli Espoti, Clara [UNESP]; Santos Sarah, Marcilene Machado dos [UNESP]; Prado, Renato de Mello [UNESP] (Springer, 2020)
Silicon (Si) combined with foliar spraying of salicylic acid (SA) can affect the absorption of this beneficial element. A study with Si non-accumulators plants (soybean and bean) observed that SA foliar spraying improved leaf absorption. However, this effect is unknown in peanut (Arachis hypogaea), a Si non-accumulator species. The aim of the present study was to assess the effect of applying Si to the leaves or roots, associated with foliar applications of SA, on Si absorption and dry weight production of peanut plants. An experiment was conducted with IAC OL4 peanut cultivars in pots filled with 6 L of sand. A randomized block design was used, in a 3 x 3 factorial scheme, as follows: Si application via leaves and roots in the form of monosilicic acid and the control (no Si) and three foliar applications of salicylic acid (0; 0.05; 0.15 mM), with five repetitions. The Si was supplied via nutrient solution (root) and leaves throughout the experiment, with three spraying treatments: at the end of the vegetative stage, onset of flowering and at the start of pod formation. The SA foliar sprayings were performed together with Si. Foliar silicon application was superior to its root counterpart at all SA concentrations. The greatest Si accumulation for root application was observed at a concentration of 0.05 mM of SA. Shoot dry weight and root dry weight production increased with Si. SA application, at a concentration of 0.05 mM, especially when associated with foliar Si, favored Si absorption and dry weight production in peanut plants. Foliar spraying of Si with the addition of salicylic acid is a new strategy for silicon supplementation in Si non-accumulators.
Keywords: Arachis hypogaea; beneficial element; Plant hormone; Leaf silicon application; Plant nutrition